Peran Pemerintah melalui Program Pelatihan dalam Mengurangi Jumlah Pengangguran Menurut Perspektif Ekonomi Islam (Studi Kasus Dinas Ketenagakerjaan Kota Medan) - Ellyza Cindi Mentari; Waizul Qarni; Nur Ahmadi Bi Rahmani (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
AbstractMedan City Employment Service in realizing the vision to reduce the number of unemployed in Medan City through a training program seen from 3 aspects, namely the realization of a competitive, prosperous and religious workforce. This research was conducted to find out how the government's role through training programs in reducing the number of unemployed according to the perspective of Islamic Economics. The research method used is qualitative by using primary data and secondary data. Data collection techniques using interviews and documentation. The research results obtained were found to be the fact that the role of the government through training programs in reducing the number of unemployed had been carried out properly in accordance with the 3 aspects of the vision of the Medan City Manpower Office and had been carried out optimally. The results of an analysis of the government's role through training programs in reducing the number of unemployed workers have not been able to reduce the number of unemployed in 2019 to 2021 due to the Covid-19 pandemic that has hit Indonesia. When viewed from the side of Islamic Economics, the government's role through the training program in reducing the number of unemployed has been responsible and fair to the training participants, but there is injustice felt by participants who come from outside the city of Medan because only those who can take part in the training program are from the city of Medan.Â Keywords: Training Programs, Unemployment and The Islamic Economy